2014
DOI: 10.1016/j.nucengdes.2013.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic evaluation and fission product identification of irradiated TRISO coated particles from the AGR-1 experiment: A preliminary review

Abstract: In this paper a brief summary of results from characterization of microstructures in the coating layers of selected irradiated fuel particles with burnup of 11.3% and 19.3% FIMA will be given. The main objectives of the characterization were to study irradiation effects, fuel kernel porosity, layer debonding, layer degradation or corrosion, fission-product precipitation, grain sizes, and transport of fission products from the kernels across the TRISO layers. Characterization techniques such as scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 8 publications
2
50
1
Order By: Relevance
“…It was for example found in the earlier studies [13] that the micron-sized Pd-rich precipitates were visible up to approximately 15 μm from the SiC/IPyC interface.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…It was for example found in the earlier studies [13] that the micron-sized Pd-rich precipitates were visible up to approximately 15 μm from the SiC/IPyC interface.…”
Section: Discussionmentioning
confidence: 73%
“…These studies further showed significant Pd corrosion on the SiC-PyC interface. However, in the AGR-1 experiment, no significant Pd corrosion is observed [13]. The Pd and Ag concentrations used in these out-of-pile research studies, are order of magnitude larger than in the actual TRISO coated particles, which could contributed to the different corrosion behaviour observed compared to those of the AGR-1 experiment.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…TEM lamellae were prepared from the SiC layer of this particle by standard focused ion beam (FIB) techniques. More information on the particle selection process and sample preparation can be found in [5] and [9].…”
Section: Methodsmentioning
confidence: 99%
“…Apart from results from the AGR-1 experiment [5][6][7], studies of Ag release through TRISO particles mostly focussed on out of reactor simulations using bulk-or epitaxial SiC wafers. In this work we investigate the migration behaviour of a Pd-Ag combination in surrogate TRISO particles containing ZrC kernels at high temperature without neutron irradiation.…”
Section: Introductionmentioning
confidence: 99%